NF-κB protects NKT cells from tumor necrosis factor receptor 1-induced death - Kumar, A; Gordy, LE; Bezbradica, JS; Stanic, AK; Hill, TM; Boothby, MR; Van Kaer, L; Joyce, S (Nature Publishing Group, 2017)
Semi-invariant natural killer T (NKT) cells are innate-like lymphocytes with immunoregulatory properties. NKT cell survival during development requires signal processing by activated RelA/NF-κB. Nonetheless, the upstream signal(s) integrated by NF-κB in developing NKT cells remains incompletely defined. We show that the introgression of Bcl-xL-coding Bcl2l1 transgene into NF-κB signalling-deficient IκBΔN transgenic mouse rescues NKT cell development and differentiation in this mouse model. We reasoned that NF-κB activation was protecting developing NKT cells from death signals emanating either from high affinity agonist recognition by the T cell receptor (TCR) or from a death receptor, such as tumor necrosis factor receptor 1 (TNFR1) or Fas. Surprisingly, the single and combined deficiency in PKC-θ or CARMA-1-the two signal transducers at the NKT TCR proximal signalling node-only partially recapitulated the NKT cell deficiency observed in IκBΔN tg mouse. Accordingly, introgression of the Bcl2l1 transgene into PKC-θ null mouse failed to rescue NKT cell development. Instead, TNFR1-deficiency, but not the Fas-deficiency, rescued NKT cell development in IκBΔN tg mice. Consistent with this finding, treatment of thymocytes with an antagonist of the inhibitor of κB kinase -which blocks downstream NF-κB activation- sensitized NKT cells to TNF-α-induced cell death in vitro. Hence, we conclude that signal integration by NF-κB protects developing NKT cells from death signals emanating from TNFR1, but not from the NKT TCR or Fas.